Pengembangan Buku Saku Berbasis Explicit Instruction Pada Mata Kuliah Hubungan Masyarakat - Intan Rachmawati Alif Dhea Prawita; Siti Sri Wulandari (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2022)
The public relations course is a science and skill-based course in the Covid-19 pandemic, students are required to do independent learning at home. From this, preliminary research was conducted with the result that there was a high level of interest and perspective on achieving PR skills in attending public relations courses, but in this case, many students did not have books to support learning. This study aims to determine the effectiveness of developing a public relations pocketbook based on explicit instruction for Office Administration Education 2019 students who take public relations courses. The method used is the research and development method with five stages of research, namely Analysis, Design, Development, Implementation, and Evaluate. In conducting the research, the data collection instrument used a study sheet (material validation, graphic validation, and language validation) while the student assessment used a questionnaire with several assessment aspects, namely (content aspects, presentation aspects, and language aspects) and besides that, there was a questionnaire to measure skills. Public relations were formed as a result of the existence of a pocketbook. The results showed a positive response from expert lecturers and students with the "Very Good" category of eligibility be used as a learning medium for public relations courses. In addition, it was found that a pocketbook answered students' perspectives regarding the development of public relations skills (communication, managerial, social networking, honesty, and creativity) which were obtained in the "Very Good" category.